Penguatan Karakter Ekonomi Anak Melalui Pembelajaran Menyenangkan: Studi Kegiatan Pengabdian Masyarakat di SD Muhammadiyah - Siti Nur Azizah Tompunu; Hasniwati; Dian Sasmita; Isma Stefani; Nur Indah Cahyani; Sri Sulaeni Arif Putri; Akbar Sakir; Sayid Ospaullah; Fahrul Fadli Adifsah; Asrahiyah Febrianti; Siti Walida Mustamin (CV. ITTC INDONESIA, 2025)
Early economic education plays an important role in shaping children's character, habits, and mindset in managing resources wisely. However, its delivery must be adapted to children's level of understanding so that basic concepts such as saving, cooperation, and distinguishing needs from wants can be grasped in a fun and meaningful way. This community service activity aimed to introduce fundamental economic concepts to elementary school students through a learning-by-playing approach. The activity was carried out by students of Universitas Muhammadiyah Makassar at a Muhammadiyah elementary school using interactive methods including economic material delivery, educational games, prayer practice, and social action. The results showed that this approach was effective in enhancing children's understanding and interest in basic economic concepts. The participants were enthusiastic, able to comprehend the material, and demonstrated behavioral changes, such as showing more appreciation for friends and understanding the importance of saving. The school welcomed the program positively and expressed hope for its continuation. Therefore, this fun and educational approach proved successful in fostering early economic literacy while simultaneously shaping positive character traits in children.